Heterologous booster vaccination with CoronaVac following prime vaccination with mRNA vaccine. Issue 8 (23rd August 2022) - Goh, Yun Shan; Fong, Siew‐Wai; Rouers, Angeline; Chang, Zi Wei; Tay, Matthew Zirui; Chavatte, Jean‐Marc; Zhuo, Nicole Ziyi; Hor, Pei Xiang; Loh, Chiew Yee; Huang, Yuling; Wong, Joel Xu En; Tan, Yong Jie; et al.
Abstract: Objective: Despite the high vaccine efficacy of mRNA COVID‐19 vaccines, there are individuals who developed excessive reactogenic and/or allergic responses after the first mRNA dose and were considered ineligible for further mRNA doses. CoronaVac, an inactivated SARS‐CoV‐2 vaccine, is recommended in Singapore as an alternative. Methods: Individuals, ineligible for further mRNA vaccines (BNT162b2 or mRNA‐1273) because of excessive reactive responses to prime mRNA vaccination, were recruited and offered two doses of CoronaVac as booster vaccination 38–224 days post their mRNA vaccine dose. Individuals who did not develop any excessive reactive responses after the prime mRNA vaccination were also recruited and given another mRNA vaccine as booster vaccination. Blood samples were collected at days 0, 21 and 90 post first CoronaVac dose and mRNA dose, respectively, for analysis. Results: We showed that two CoronaVac booster doses induced specific immunity in these mRNA vaccine‐primed individuals. Although the spike‐specific antibody response was lower, their memory B cell response against the receptor‐binding domain (RBD) of the spike protein was similar, compared with individuals who received two BNT162b2 injections. The spike‐specific memory T cell response also increased following CoronaVac booster doses. However, specific immunity against the Omicron variant was low, similar to individuals with two BNT162b2 doses. Conclusion: Our findings showed that while mRNA vaccine‐primed individuals can opt for two subsequent doses of CoronaVac, an additional dose may be necessary to achieve protection, especially against newly emerging immune escape variants such as Omicron. Abstract : Individuals, ineligible for further mRNA vaccines because of excessive reactive responses to prime mRNA vaccination, were recruited and offered two doses of CoronaVac as booster vaccination. Individuals who did not develop any excessive reactive responses after the prime mRNA vaccination received another mRNA vaccine as booster vaccination. Blood samples were collected at days 0, 21 and 90 post first CoronaVac dose and mRNA dose, respectively, and the antibody profiles, B and T cell responses, were analysed.